Inflammatory markers in children with obstructive sleep apnea syndrome - Wang, Yingge; Chen, Ying; Lin, Wei; Huang, Min; Xu, Yuanteng; Chen, Guohao (Frontiers in Pediatrics, 2023)
Objective: To evaluate serum inflammatory markers of YKL-40, Interleukin-6 (IL-6), Interleukin-8(IL-8), Interleukin-10(IL-10), TNF-α( tumor necrosis factor-α)and CRP (C-reactive protein)in children with and without OSAS. Methods: The technique of ELISA has been used to identify the concentration of the inflammatory markers such as YKL-40, IL-6, IL-8, IL-10, TNF-α, and CRP in the serum of 83 children with OSAS and 83 children without OSAS. Results: Serum levels of YKL-40, IL-6, IL-8, and IL-10 were found to be increased in children with OSAS. YKL-40 was found to be positively correlated with IL-6 and IL-8, and negatively correlated with IL-10. At the same time,YKL-40 was also found to be positively correlated with OAHI and LoSpO2% in OSAS group. IL-8 was positively correlated with OAHI whereas IL-10 was positively correlated with LoSpO2.Conclusion: Children with OSAS is in a systemic inflammatory state. YKL-40 together with IL-8 may act as serum inflammatory markers and provide indication for the diagnosis of children with OSAS.